At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
We have to use the chain rule's
[tex]f(x)=ln(17-x)[/tex]
[tex]f[g(x)]=ln[g(x)][/tex]
therefore
[tex]f(u)=ln(u)[/tex]
and
[tex]u=g(x)=17-x[/tex]
them we have
[tex]f'(x)=f'(u)*g'(x)[/tex]
[tex]f'(u)=\frac{1}{u}[/tex]
[tex]g'(x)=-1[/tex]
[tex]f'(x)=f'(u)*g'(x)[/tex]
[tex]f'(x)=\frac{1}{u}*(-1)[/tex]
[tex]f'(x)=-\frac{1}{u}[/tex]
[tex]\boxed{\boxed{\therefore~f'(x)=-\frac{1}{17-x}}}[/tex]
[tex]f(x)=ln(17-x)[/tex]
[tex]f[g(x)]=ln[g(x)][/tex]
therefore
[tex]f(u)=ln(u)[/tex]
and
[tex]u=g(x)=17-x[/tex]
them we have
[tex]f'(x)=f'(u)*g'(x)[/tex]
[tex]f'(u)=\frac{1}{u}[/tex]
[tex]g'(x)=-1[/tex]
[tex]f'(x)=f'(u)*g'(x)[/tex]
[tex]f'(x)=\frac{1}{u}*(-1)[/tex]
[tex]f'(x)=-\frac{1}{u}[/tex]
[tex]\boxed{\boxed{\therefore~f'(x)=-\frac{1}{17-x}}}[/tex]
[tex]y'=(17-x)'\cdot \frac{1}{ln(17-x)} =- \frac{1}{ln(17-x)} \\\\ \ \ and\ \ \ D: \ 17-x > 0\ \ \ \Rightarrow\ \ \ x<17\ \ \ \Rightarrow\ \ \ D=(17;+\infty)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.